PENGARUH UKURAN PERUSAHAAN, REPUTASI AUDITOR, DAN FAKTOR LAINNYA TERHADAP AUDIT REPORT LAG - Muhammad Arief Effendi; Vina Sugiana Tirtajaya (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence related to the effect of firm size, auditor reputation, solvency, profitability, liquidity, board size, and firm age on audit report lag. This research uses a population of non-financial companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020. Sampling in this research using purposive sampling method so it requires criteria for taking samples. This research examined 182 companies and total 546 data which will be researched using multiple linear regression. The results showed that firm size had a positive effect on audit report lag, while board size and firm age had a negative effect. However, auditor reputation, solvency, profitability, and liquidity have no effect on audit report lag